Development of an interferometric scattering microscope for high-speed and high-sensitivity imaging of single particles - Yong, Zane (Nanyang Technological University, 2024)
The single particle tracking (SPT) method has significantly advanced our understanding of protein dynamics and interactions, providing crucial insights into the functional mechanisms vital for life sciences applications. Despite its successes, traditional SPT methods, which primarily use fluorescence and scattering-based labeling, face challenges such as photobleaching and limited observation durations, restricting their efficacy in tracking smaller nanoparticles. This report details the development of a label-free SPT approach using the interferometric scattering microscopy (iSCAT) technique in Prof. Tong Ling's lab. iSCAT is an exceptionally sensitive imaging method that substantially enhances the visibility of light scattered by nanoscopic objects. In this study, we designed and constructed a wide field iSCAT setup and characterized it using gold nanoparticles (AuNPs) and proteins. Additionally, we employed advanced image processing techniques and a Python-based data analysis pipeline to successfully extract quantitative data from both AuNPs and single proteins. Our preliminary results establish a correlation between molecular mass and interferometric contrast